Differentiation of CD133-positive pancreatic cells into insulin-producing islet-like cell clusters - Koblas, T; Pektorova, L; Zacharovova, K; Berkova, Z; Girman, P; Dovolilova, E; Karasova, L; Saudek, F (Transplantation proceedings, 2008)
Adult pancreatic stem and progenitor cells could represent an alternative source of insulin-producing tissue for diabetes treatment. In order to identify these cells, we have focused on the human pancreatic cells expressing cell surface molecule CD133, a marker of adult stem cells. We found that population of human CD133-positive pancreatic cells contains endocrine progenitors expressing neurogenin-3 and cells expressing human telomerase, ABCG2, Oct-3/4, Nanog, and Rex-1, markers of pluripotent stem cells. These cells were able to differentiate into insulin-producing cells in vitro and secreted C-peptide in a glucose-dependent manner. Based on our results, we suppose that the CD133 molecule represents another cell surface marker suitable for identification and isolation of pancreatic endocrine progenitors.
Keywords: buněčná diferenciace; Antigens, CD; CD antigeny; Humans; Islets of Langerhans; RNA; Magnetics; antigen AC133; C-Peptide; magnetismus; polymerázová řetězová reakce s reverzní transkripcí; C-peptid; separace buněk; lidé; Reverse Transcriptase Polymerase Chain Reaction; peptidy; pankreas; Pancreas; Peptides; glykoproteiny; Glycoproteins; Cell Differentiation; Cell Separation; Langerhansovy ostrůvky; Cell Culture Techniques; AC133 Antigen; buněčné kultury